Kesesuaian Bakat dalam Olahraga Sepakbola pada Siswa SSB Tri Cakti Semarang Usia 11 – 12 Tahun 2021 - Asmoro, Rayhan; Rustiadi, Tri (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of the study was to determine the level of talent of SSB Tri Cakti Semarang students aged 11-12 years in the sport of soccer. This research method uses a descriptive method with a sports search talent scouting survey technique through a quantitative percentage approach. The research population was 75 students and the sample was 21 students, taken using purposive sampling technique. The research instrument used a sport search model talent scouting test. The results of the study showed as many as 25 students. As for the group there (28%) are very talented in the sport of soccer. There are (4%) talented, moderately talented, and less talented in the sport of soccer. And there are also (60%) not talented. 18 students do not match between their talents. The conclusion is that 7 students have very gifted criteria, 1 student has gifted criteria, 1 student is quite talented, 1 student is less talented, and 15 students are not gifted. Researchers suggest for SSB Tri Cakti Semarang to do a Sport Search test to find out the talent results of the students in the team so that the coach can find out the results of student deficiencies. For students who still have poor performance, they must improve the pattern of practice in order to reach the existing standard.